Safety and efficacy of intensive vs. guideline antiplatelet therapy in high-risk patients with recent ischemic stroke or transient ischemic attack: rationale and design of the Triple Antiplatelets for Reducing Dependency after Ischaemic Stroke (TARDIS) trial (ISRCTN47823388) - Beridze, M.; Christensen, H.; Dineen, Robert A.; Duley, Lelia; Heptinstall, Stan; James, M.; Markus, H.S.; Pocock, S; Ranta, A.; Robinson, T.; Nikola, N.; Venables, G.; et al. (Wiley, 2015)
RATIONALE: